Body mass index strongly impacts the diagnosis and incidence of heparin-induced thrombocytopenia in the surgical intensive care unit. Issue 3 (March 2016) - Bloom, Matthew B.; Zaw, Andrea A.; Hoang, David M.; Mason, Russell; Alban, Rodrigo F.; Chung, Rex; Melo, Nicolas; Volod, Oksana; Ley, Eric J.; Margulies, Daniel R.
Abstract : BACKGROUND: The obese state has been linked to several immune-mediated conditions. Our objective was to examine the association of body mass index (BMI) with the diagnosis of heparin-induced thrombocytopenia (HIT). METHODS: Prospectively collected data on patients in the surgical and cardiac intensive care unit suspected of having HIT between January 2007 and August 2014 were analyzed. Patients were categorized into five discrete BMI (kg/m 2 ) groups and compared. Data collected included Warkentin 4-T scores, antiplatelet factor 4 (anti-PF4OD ) values, serotonin release assay values, and thromboembolic diseases. HIT positivity was defined as serotonin release assay value greater than 20%. RESULTS: Of 304 patients meeting inclusion criteria, mean (SD) age was 62.1 (16.5) years, 59% were male, and mean (SD) BMI was 27 (6) kg/m 2 . Thirty-six (12%) were positive for HIT. Incidence of HIT increased progressively with BMI (0%, 8%, 11%, 19%, 36%; p < 0.001). Compared with patients with normal BMI, patients with a BMI of 30 kg/m 2 to 39.9 kg/m 2 had a 200% increase in the odds for HIT (odds ratio [OR], 2.94; 95% confidence interval [CI], 1.20–7.54; p = 0.019), while patients with a BMI of 40 kg/m 2 or greater had a 600% increase (OR, 6.98; 95% CI, 1.59–28.2; p = 0.012). After regression analysis, BMI remained an independent predictor of the development of HIT (adjusted OR per kg/m 2, 1.08; 95% CI, 1.02–1.14; p = 0.010). Anti-PF4OD values greater than or equal to 2.0 also increased with BMI ( p < 0.001). In-hospital mortality increased significantly with BMI above normal ( p = 0.026). Warkentin 4-T scores, deep venous thrombosis, pulmonary embolism, and stroke incidence did not correlate with changes in BMI. CONCLUSION: Increasing BMI seems to be strongly associated with increased rates of HIT in intensive care unit patients. Obesity is an important new clinical variable for estimating the pretest probability of HIT, and patient "thickness" could be considered a fifth "T" of the 4-T scoring system. Additional biochemical work is indicated to decipher the role of obesity in this immune-mediated condition. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III.